Measures of Parent Engagement for Children Receiving Developmental or Rehabilitation Interventions: A Systematic Review. (1st January 2018) - D'Arrigo, Rachel; Ziviani, Jenny; Poulsen, Anne A.; Copley, Jodie; King, Gillian
ABSTRACT: Aim : To examine the conceptual and clinometric properties of measures for parent engagement in developmental or rehabilitation interventions for children and youth (<18 years of age). Methods : Four electronic databases were searched. Studies were included if they reported measures of at least one domain of parent engagement (i.e. affective, cognitive or behavioral). Reviewers independently identified measures and evaluated studies using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) and the CanChild Outcome Measures Rating Form. Results : A total of 9, 500 unique papers were retrieved, and 36 reported parent engagement measurement. Four measures met inclusion criteria: the Parent Involvement Index (PII), the Parent Participation Measure (PPM), the General Adherence subscale of the Medical Outcomes Study (GAMOS) and the Triadic Intervention and Evaluation Rating Scale (TIERS). No measure captured all domains of in-session parent engagement. Two addressed out-of-session parent engagement. There were limitations in validity and reliability. Conclusions : Few measures of parent engagement are available. Existing measures mostly captured the behavioral domain of in-session engagement, and none assessed cognitive or affective aspects of engagement. Out-of-session engagement was infrequently captured. There is currently no comprehensive measure of parent engagement in pediatric developmental and rehabilitation services that demonstrates good clinical utility or is conceptually and psychometrically sound.